Self-government nomenclature for panchayats - Mandal, Amal (1999)
With focus on instrumentalities of self-governance of panchayat raj bodies, the author analyses the provisions in Central and State PR Acts, the critical issue of exercising powers and apprehensions thereof affecting effective and autonomous discharge of developmental functions between Centre and States, and denial of overall control to Gram Sabha, the author, in the light of experiences in Maharashtra and Gujarat during 60s and Karnataka and West Bengal during 70s and 80s, concludes that strength of PRIs is mainly correlated to the political game-plan of ruling political parties. - Reproduced
Keywords: Panchayat